The Configurative Role of Emptiness in Hylectic Consciousness: A Phenomenological Investigation - Amar Yanuar Pamungkas (Jurnal Filsafat "WISDOM", 2026)
Husserl’s Ideas I distinguishes a noetic approach from a hyletic (material) one, yet his emphasis on the former leaves the latter conceptually underdeveloped. This underdevelopment fuels familiar objections: the enigmatic status of non-intentional “data,” worries about immanentism and idealist drift, and suspicions that correlationism licenses a tacit humanism. I offer a critical reconstruction of the hyletic dimension that preserves Husserl’s texts while clarifying its role in phenomenological analysis. Methodologically, I conjoin a conceptual analysis of hyletic and noetic moments with a phenomenological account of their correlation in givenness (Gegebenheit). The claim is that hyletic content, through distinctive modes of “emptiness,” functions configuratively, structuring intentional experience rather than simply stocking it with data. On this view, the hyletic is not brute sensory matter but a condition for what I call epistemic reversibility within consciousness: the capacity of experience to reconfigure its own evidential bearings by way of hyletic modulation. This reinterpretation addresses the standard critiques and repositions hyletics as an internally normative moment of Husserlian phenomenology.